African Initiated Christianity and the Decolonisation of Development Sustainable Development in Pentecostal and Independent Churches - Öhlmann, Philipp; Gräb, Wilhelm; Frost, Marie-Luise (Routledge Research in Religion and Development, 2020)
This book investigates the substantial and growing contribution which African Independent and Pentecostal Churches are making to sustainable development in all its manifold forms. Moreover, this volume seeks to elucidate how these churches reshape the very notion of sustainable development and contribute to the decolonisation of development. Fostering both overarching and comparative perspectives, the book includes chapters on West Africa (Nigeria, Ghana, and Burkina Faso) and Southern Africa (Zimbabwe and South Africa). It aims to open up a subfield focused on African Initiated Christianity within the religion and development discourse, substantially broadening the scope of the existing literature. Written predominantly by scholars from the African continent, the chapters in this volume illuminate potentials and perspectives of African Initiated Christianity, combining theoretical contributions, essays by renowned church leaders, and case studies focusing on particular churches or regional contexts. While the contributions in this book focus on the African continent, the notion of development underlying the concept of the volume is deliberately wide and multidimensional, covering economic, social, ecological, political, and cultural dimensions. Therefore, the book will be useful for the community of scholars interested in religion and development as well as researchers within African studies, anthropology, development studies, political science, religious studies, sociology of religion, and theology. It will also be a key resource for development policymakers and practitioners.